PERLINDUNGAN HUKUM BAGI PEMEGANG HAK ATAS TANAH DALAM PENETAPAN GANTI RUGI TERKAIT DENGAN PENGADAAN TANAH UNTUK KEPENTINGAN UMUM - Rizky Amalia (Yuridika, 2012)
Land acquisition is done by way of release or transfer of land rights of the holders of rights over land to government agencies that require ground. As a form of respect for the rights of holders of land rights, which require land-party in this case is the government agency, provide appropriate compensation on the basis of agreement between both parties through consultation. Form of legal protection given to holders of land rights is the determination of compensation based on the deliberations, the proper compensation that can provide a better survival than the level of socio-economic life before the affected land acquisition, and submission of objections to the amount of indemnification. Custody compensation cannot be the basis for taking land holders of land rights by Government agencies that require ground.Key Words : land acquisition, legal protection, custody compensation.